Distribuidores Textiles S.A. (DITEXSA) - Valdés Palacio, Armando (1993)
This case study presents the situation of a clothing company with many years of operation that is affected when the entry into the market of department stores, or large retailers, causes changes in the distribution system of its products. The discussion should focus on four objectives: first, to get the participants in the discussion to analyze the physical distribution situation before the intervention of large retailers, and to explain how their appearance in the market affects the industrial or commercial company and two main distributors of a product line; second, to get the participants to assume the roles of company executives and reach a joint decision on how to relate to the elements of the distribution chain without affecting the cordial relations with their long-standing customers; third, to motivate participants to become aware of the importance for the company of changes in its environment, in this case, in physical distribution, distribution channels and the relationships between producers, the distribution chain and end customers; finally, to evaluate the aspects to be considered in the design of distribution channels and to study the advisability of making changes in channel participation and in the use of multiple or dual channels.